Analisis Perbandingan Performa Algoritma Round Robin dan Least Connection untuk Load Balancing pada Software Defined Network - Agung Nugroho; Widhi Yahya; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
The development of internet technology whom the users desire for the availaible services anytime tend to be increased following the current development which commonly not always supported by the increasing adequate server services. The highest users demand make the work load in server raised rapidly which cause down server in a short period along with the needs of technology which handle the utilization of complex connections. As a new technology, Software defined network offers scalability and programmability for the using of connections which become complex such as Balancing Web Server. There are some studies concerning with load balancing in Software defined network (SDN) with various algorithm which is applied will resulted difference performance from algorithm, , one of them is Round robin and Least connection. The experiment is done with 3 categories; low, medium, and high. The experiments parameter which is used are Throughput, Response time, and CPU Usage use Httperf and Psutil. Round robin Algorithm is more excellent than Least connection Algorithm in a tiny connection. On the other hand, for the bigger connection, Least connection Algorithm is excellent. The average value of time response shows the superiority of Round robin Algorithm rather than Least connection Algorithm. CPU Usage server with the Round robin Algorithm is more stable in each rate category. On the contrary, Least connection Algorithm is less of load than Round robin Algorithm in spite of the value is raise in each rate category.